Pengolahan Limbah Organik Kulit Pisang (Musa balbisiana) dan Kubis (Brassica oleracea) menjadi Eco Enzyme - Aziza Putri Ana; Desy Kurniawati; Iswendi Iswendi (MASALIQ, 2025)
The management of household organic waste presents a significant challenge in efforts to promote environmental sustainability. This study aims to utilize banana peels (Musa balbisiana) and cabbage (Brassica oleracea) waste as raw materials for the production of eco-enzyme through a three-month fermentation process using a ratio of 3:1:10 (organic waste:brown sugar:water). The evaluation included organoleptic tests (color and aroma), pH measurement, and qualitative analysis of nitrogen (N), phosphorus (P), and potassium (K) content. The results showed that both eco-enzyme variations exhibited a cloudy brown color, acidic aroma with varying banana peel scent intensity, and a pH of 3, indicating high acidity due to organic acid formation. Qualitative tests confirmed the presence of N, P, and K in both variations. These findings demonstrate the potential of combining banana peels and cabbage to produce eco-enzyme as an environmentally friendly organic fertilizer. Further research is recommended to conduct quantitative analysis to determine nutrient content levels and assess the effectiveness of eco-enzyme application in agricultural practices.